Lactylation of HDAC1 Confers Resistance to Ferroptosis in Colorectal Cancer - Zhou Yang; Wei Su; Qinglin Zhang; Lili Niu; Baijie Feng; Yu Zhang; Feng Huang; Jiaxin He; Qinyao Zhou; Xin Zhou; Longjun Ma; Jingwan Zhou; et al. (Advanced Science)
Abstract Colorectal cancer (CRC) is highly resistant to ferroptosis, which hinders the application of anti‐ferroptosis therapy. Through drug screening, it is found that histone deacetylase inhibitor (HDACi) significantly sensitized CRC to ferroptosis. The combination of HDACi and ferroptosis inducers synergically suppresses CRC growth both in vivo and in vitro. Mechanically, HDACi reduces ferroptosis suppressor protein (FSP1) by promoting its mRNA degradation. Specifically, it is confirmed that HDACi specifically targets HDAC1 and promotes the H3K27ac modification of fat mass‐ and obesity‐associated gene (FTO) and AlkB Homolog 5, RNA Demethylase (ALKBH5), which results in significant activation of FTO and ALKBH5. The activation of FTO and ALKBH5 reduces N6‐methyladenosine (m6A) modification on FSP1 mRNA, leading to its degradation. Crucially, lactylation of HDAC1K412 is essential for ferroptosis regulation. Both Vorinostat (SAHA) and Trichostatin A (TSA) notably diminish HDAC1K412 lactylation in comparison to other HDAC1 inhibitors, exhibiting a consistent trend of increasing susceptibility to ferroptosis. In conclusion, the research reveals that HDACi decreases HDAC1K412 lactylation to sensitize CRC to ferroptosis and that the combination of HDACi and ferroptosis inducers can be a promising therapeutic strategy for CRC.